2013
DOI: 10.1186/1471-2318-13-108
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the body posture of women occurring with age

Abstract: BackgroundA current topic in the field of geriatrics still needing a great deal of study is the changes in body posture occurring with age. Symptoms of these changes can be observed starting between the ages of 40–50 years with a slow progression that increases after 60 years of age. The aims of this study were to evaluate parameters characterizing the posture of women over the age of 60 years compared with a control group and to determine the dynamics of body posture changes in the following decades.MethodsTh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
65
1
6

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(82 citation statements)
references
References 28 publications
4
65
1
6
Order By: Relevance
“…In optics, the physical basis of this method is called the Moire phenomenon. [17] Scientific studies have confirmed that the results obtained by the photogrammetric method are very close to X-ray outcomes. [18,19] Photogrammetry has been demonstrated to be a reliable method for the measurement of postural deviations from the posterior and lateral views.…”
Section: Methodsmentioning
confidence: 65%
“…In optics, the physical basis of this method is called the Moire phenomenon. [17] Scientific studies have confirmed that the results obtained by the photogrammetric method are very close to X-ray outcomes. [18,19] Photogrammetry has been demonstrated to be a reliable method for the measurement of postural deviations from the posterior and lateral views.…”
Section: Methodsmentioning
confidence: 65%
“…This lumbar lordotic motion reportedly contributes to shoulder elevation. Drzał-Grabiec and colleagues evaluated parameters characterizing the posture of women over the age of 60 years compared with a control group to determine the dynamics of body posture changes in the following decades [1]. They found that thoracic kyphosis depth significantly deepened with age and there were statistically significant differences in the thoracic-lumbar spine slope and upper thoracic spine slope while the lumbar spine slope did not show significant differences between age groups.…”
Section: Discussionmentioning
confidence: 99%
“…Kyphotic spinal deformities are common among the elderly [1]. A reduction in the lumbar lordosis angle (LL) and pelvic tilt angle (PT) are also characteristic of aging.…”
Section: Introductionmentioning
confidence: 99%
“…Kejadian kifosis toraks meningkat dengan usia. Peningkatan asimetris tersebut menunjukkan secara signifikan bahwa sudut kifosis toraks lebih tinggi dari garis bahu dan perbedaan ketinggian sudut bahu terendah pada pengukuran kelompok wanita yang lebih tua (13 Setelah melakukan latihan 6 kali P1 menunjukkan bahwa masih mengalami gemetar saat menggerakkan tangan terlalu lama. Hal tersebut sesuai dengan pernyataan berikut:…”
Section: P1 P3unclassified